Laboratory testing in patients treated with direct oral anticoagulants: a practical guide for clinicians. (28th December 2017) - Douxfils, J.; Ageno, W.; Samama, C.‐M.; Lessire, S.; ten Cate, H.; Verhamme, P.; Dogné, J. ‐M.; Mullier, F.
Abstract : Click to hear Dr Baglin's perspective on the role of the laboratory in treatment with new oral anticoagulants Summary: One of the key benefits of the direct oral anticoagulants (DOACs) is that they do not require routine laboratory monitoring. Nevertheless, assessment of DOAC exposure and anticoagulant effects may become useful in various clinical scenarios. The five approved DOACs (apixaban, betrixaban, dabigatran etexilate, edoxaban and rivaroxaban) have different characteristics impacting assay selection and the interpretation of results. This article provides an updated overview on (i) which test to use (and their advantages and limitations), (ii) when to assay DOAC levels, (iii) how to interpret the results relating to bleeding risk, emergency situations and perioperative management, and (iv) what is the impact of DOACs on routine and specialized coagulation assays. Assays for anti‐Xa or anti‐IIa activity are the preferred methods when quantitative information is useful, although the situations in which to test for DOAC levels are still debated. Different reagent sensitivities and variabilities in laboratory calibrations impact assay results. International calibration standards for all specific tests for each DOAC are needed to reduce the inter‐laboratory variability and allow inter‐study comparisons. The impact of the DOACs on hemostasis testing may cause false‐positive or false‐negative results; however, these can be minimized by using specific assays and collecting blood samples at trough concentrations. Finally, prospective clinical trials are needed to validate the safety and efficacy of proposed laboratory thresholds in relation to clinical decisions. We offer recommendations on the tests to use for measuring DOACs and practical guidance on laboratory testing to help patient management and avoid diagnostic errors.